Participatory governance and trans-sectoral mobilities: The new dynamics of adaptive preferences in the case of transport planning in Seoul, South Korea. (May 2017) - Shin, HaeRan; Lee, Kyungeun
Abstract: This study looks at how adaptive preferences develop in participatory governance characterised by the trans-sectoral mobility of key actors in the context of a transport planning project in Seoul. The mayor of the city, who used to be an influential civil society figure, and his former colleagues, moved from the civil society sector to government. Based on participant observation in one such negotiation and at public hearings, in-depth interviews with key members, and archival analysis, this research argues that first, trans-sectoral mobilities and increased opportunities for participation enabled opponents of the light rail to see the problem of limited access to information and lack of knowledge transfer. The opponents faced constraints of transparency; a condition that the Seoul government argued was inevitable due to the need for confidential information and lack of expertise on the part of opponents of the plan. Second, at the same time, opponents developed an adaptive preference for dropping opposition to the plan based on a long-term political opportunity structure, as well as political support towards the mayor, in the context of the domain of national politics. By examining how they develop such adaptive preferences despite expanded opportunities for participation, this research contributes to the debate on the dynamics of participatory governance. Highlights: Actors' moves across sectors brought about new dynamics of participatory governance. Opponents of the light railway construction criticised the lack of transparency. Opponents developed adaptive preferences based on long-term opportunities. The adaptive preferences led them to withdraw rather than continue to criticise.